1987
DOI: 10.1002/ijc.2910390402
|View full text |Cite
|
Sign up to set email alerts
|

Use of oral contraceptives and risk of invasive cervical cancer in previously screened women

Abstract: Within the context of a larger hospital-based case-control study carried out to assess the efficacy of cervical cancer screening, the possible association between oral contraceptives and risk of invasive cervical cancer has been studied as well. Because in the GDR cytological screening is an integral part of the gynaecological basic care, only a few women reported oral contraceptive use but had no Pap-smears in that study. Thus, the analysis was confined to those 129 cases and 275 controls who had at least one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 13 publications
3
9
0
Order By: Relevance
“…These findings augment previous reports where a direct relation of child-bearing to cervical cancer had been reported (EBELING et al 1987). With reference to nulliparous women, the risk of invasive cervical cancer was reported to increase significantly with increasing number of births; the risk being about 5 times greater in women with 5 or more births (PARAZZINI et al 1992).…”
Section: Discussionsupporting
confidence: 85%
“…These findings augment previous reports where a direct relation of child-bearing to cervical cancer had been reported (EBELING et al 1987). With reference to nulliparous women, the risk of invasive cervical cancer was reported to increase significantly with increasing number of births; the risk being about 5 times greater in women with 5 or more births (PARAZZINI et al 1992).…”
Section: Discussionsupporting
confidence: 85%
“…Among studies that contributed to the present collaborative reanalysis, four cohort studies did not include information on sexual behavior (25)(26)(27)(28). Findings on sexual behavior have been published from eight studies that were not included and were consistent with our present results (14,(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Discussionsupporting
confidence: 70%
“…Data could not be retrieved for 10 published studies [14][15][16][17][18][19][20][21][22][23][24] and 1 research group 25 declined to take part in the collaboration. Of the studies identified, original data were available from 25,6, and all had information on reproductive factors and were therefore included in the present collaborative reanalysis (Table I).…”
Section: Resultsmentioning
confidence: 99%
“…The results of these studies were consistent with our present results. 16,17,19,[21][22][23][24] The difficulty of disentangling the effect of reproductive variables from sexual behaviour and HPV infection cannot, however, be overstated. If the number of sexual partners is inaccurately reported, or information on some potentially relevant aspects of sexual behaviour (e.g., husband's sexual behaviour in our present reanalysis) is not available, a residual confounding effect cannot be completely ruled out.…”
Section: Discussionmentioning
confidence: 99%